Women as skilled Labour: a Review of Issues, Challenges and Prospects - Masidah, Abdul Majid; Wardah Fatimah, Mohammad Yusoff; Abdul Razak, Sapian (2018)
As an important sector in the economy of Malaysia, the prolong problem of shortage of local skilled labour which the construction is experiencing may affect the sustainability of the sector and impinge it significant roles. Currently, the industry has to import foreign workers in order to fulfil the demand for manual labour. Although the government has implemented various strategy including attracting new entries among local youth so that they can be trained in construction academies, the problem still occurs. It indicates that there is a need now for a new strategy as an alternative to the present approaches. At this instance, the strategy which has not formally being ap-plied in the construction industry of Malaysia is attraction of local women to become construction skilled labour. This paper presents a review on the issue, challenges and prospect for women to be attracted as skilled labour for the construction industry of Malaysia. This paper suggested that there is potential for Malaysian women to become manual trades workers based on the literature findings that wom-en have the capability and was once a significant skilled labour in the construction industry